PENGARUH VARIETAS KACANG TANAH DAN WAKTU TANAM JAGUNG MANIS TERHADAP PERTUMBUHAN DAN HASIL PADA SISTEM TUMPANGSARI - Lukman Nulhakim; Muhammad Hatta (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2008)
Effect of Ground Nut Varieties and Sweat Corn Planting Time through Intercropping System on Growth and Yield of the Two Plants Lukman Nulhakim dan Muhammad Hatta Fakultas Pertanian Unsyiah Darussalam Banda Aceh ABSTRACT The aim of this research was to know the effect of sweat corn planting time and ground nuts varieties, and interaction between them, on both growth and yield in intercropping system. This research was conducted at Cot Cut village, Kota Baro regency, Aceh Besar sub district, from June to October 2007. Treatments were arranged by Factorial Completely Randomized Block Design 3 x 4 with 3 replicates. Sweat corn planting time consisted of 0, 15, 30 and 45 days after ground nut planting, and ground nuts varieties consisted of Putih, Merah and Gajah. Each plot were 3,5 m x 3,5 m in size, the planting spacing for sweat corn was 100 cm x 75 cm, and for ground nut was 25 cm x 25 cm. Manure was 12,25 kg/plot, applicated 1 week before ground nut planting. Urea for ground nuts was 0,12 kg/plot, applicated at ground nuts planting. Urea for sweat corn was 0,37 kg/plot, applicated 1 week after each planting times. TSP and KCl were given at ground nut planting. The results showed that 0 day after ground nut planting was the best for sweat corn growth, but 15 days after ground nut planting was the best for sweat corn yield. Variety of Putih was the best for both plants growth and yield. There was interaction between both treatments on ear of sweat corn diameters. The best combination was Putih variety planted at the same time with sweat corn